2021
DOI: 10.2478/agriceng-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Reeze-Drying Impact on Hardness of Selected Soft Fruit Liophilisates

Abstract: The objective of the paper was to describe the impact of freeze-drying conditions on hardness of lyophilizates obtained based on soft fruit pomace. Raspberry, cherry, and grape pomace from the pressing process carried out with a low-speed rotary press constituted a research material. Immediately after the pressing process, pomaces were placed in forms, frozen, and after freezing they were freeze-dried in the pressure of 20, 42, 63, 85 and 110 Pa. The obtained lyophilizates were subjected to the measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Raspberry powders obtained after the dehydration of whole fruit or pomace can be added as functional additives (e.g., natural dyes) to food preparations. In most studies, powders were obtained from drying whole fruits [ 19 , 20 ]; only a few studies concern the drying of raspberry pomace [ 21 ]. Previous findings suggest that powders obtained by spray-drying raspberry extracts could be used as natural colorants or antioxidants [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raspberry powders obtained after the dehydration of whole fruit or pomace can be added as functional additives (e.g., natural dyes) to food preparations. In most studies, powders were obtained from drying whole fruits [ 19 , 20 ]; only a few studies concern the drying of raspberry pomace [ 21 ]. Previous findings suggest that powders obtained by spray-drying raspberry extracts could be used as natural colorants or antioxidants [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drying studies of whole raspberries have shown that these techniques affect the physical properties, bioactive compounds, and antioxidant activity of the resulting powders differently [ 19 ]. Previous studies have shown that freeze-drying causes changes in the physical properties of raspberry pomace [ 21 ]. Only a few data describe the antioxidant properties of processed raspberry byproducts [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%